How Long Is Now | Final Year Project 2023 Film | Project Book - Yang, Haolin (Nanyang Technological University, 2023)
"How Long Is Now" is a captivating journey chronicling the challenges and triumphs of a team of filmmakers embarking on a 1400KM journey to shoot their latest film. Spanning across vast landscapes at Malaysia, this book documents the unexpected obstacles and moments of sheer magic that come with creating art amidst the chaos of the unknown. With heart, and raw honesty, the team's experience of pushing their boundaries and overcoming obstacles serves as a testament to the importance of passion, creativity, and perseverance in the face of adversity. Ultimately, "How Long Is Now" is a celebration of the transformative power of storytelling and the limitless possibilities that come with embracing the journey.